Mexico 2006-2012 : Creating the Foundations for Equitable Growth - World Bank (Washington, DC, 2012)
The chapters, or "policy notes," of this report, creating the foundations for equitable growth in Mexico 2006-2012, are dedicated to trying to solve parts of the puzzle as to why Mexico's level of economic development has failed to approach the level of its NAFTA trading partners, or the level of a typical OECD member state. Each chapter of this new report uses the 2000 policy notes as a reference. In this report, the authors have tried to be selective on the issues, and they explored multi-sector issues by joining themes such as education and labor markets in one chapter, or health and old age security in a single chapter. In this overview, the authors set the stage by outlining the common themes and messages that emerge from the eleven chapters of this report. There are three themes that are highlighted: 1) Mexico can do better; 2) Mexico is between two worlds and there are two worlds within Mexico. Mexico's standards of living, human and physical capital and institutions are all quite advanced compared to low income countries or compared to lower middle income countries in Latin America. On the other hand, Mexico lags far behind OECD averages. Within Mexico, there is a further dichotomy due to the high degree of inequality across individuals and across regions; 3) Policies for equitable growth are the answer. In the chapters of this report, it is emphasized that institutional change is the key to improving the regulation and performance of both the public and private sectors. The authors also highlight that restructuring government spending in a variety of sectors-in particular, establishing a more progressive allocation of spending-would be the key to initiating a phase of more growth and more equitable growth. Finally, they note that despite progress in improving economic and environmental stability in Mexico, there is still a remaining agenda of reform to assure sustainability.